Overcoming Challenges of Renewable Energy on Future Smart Grid - J.O. Petinrin J.O. Petinrin; M. Shaaban M. Shaaban (Universitas Ahmad Dahlan, 2012)
The increasing complexity of the conventional grid due to population growth, advancement in technology, and infrastructures are the factors that contribute immensely to instability, insecurity, and inefficiency of the use of electrical energy. To overcome the problems, the environmental energy sustainability calls for the use of renewable energy for sustainability of power supply. Intermittency and fluctuation of the renewable energy is a great challenge on the smart grid. This paper reveal the potential challenges of renewable energy on the smart grid and proffer solution with the application of high voltage DC (HVDC) and Flexible AC transmission system (FACTS) devices. The functions and advantages of FACTS devices are presented in this paper. Voltage control and stability control with FACTS application are also discussed because FACTS has fast controllability and capability to exchange active and reactive power independently.